2019
DOI: 10.1002/ecs2.2674
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling effects of invasive species and habitat while accounting for observer error in a long‐term amphibian study

Abstract: The invasive American bullfrog (Lithobates catesbeianus) and a variety of non‐native sport fish commonly co‐occur in lowland lentic habitats of the western United States. Both invasive taxa are implicated in declines of native amphibians in this region, but few long‐term studies of communities exist. Further, field studies of invasive–native interactions are complicated by confounding habitat modifications and observation errors. We surveyed amphibians and measured habitat characteristics for 12 yr across 38 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 91 publications
(171 reference statements)
1
22
0
Order By: Relevance
“…While bullfrogs have been implicated with amphibian declines, much of this work was correlative and potentially explained by confounding variables, such as non-native fish or disease (Hayes and Jennings 1986), or was experimental (Lawler et al 1999, Adams 2000, which may amplify effects not seen in the wild. In field studies within the Pacific Northwest, most studies have found no effect of bullfrog presence on native amphibian species occurrence (Richter and Azous 1995, Adams et al 1998, 2011, Adams 1999, Pearl et al 2005, but see Rowe et al 2019). It is possible that our native amphibian assemblage was not as susceptible to bullfrogs due to their use of terrestrial habitats post-metamorphosis.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…While bullfrogs have been implicated with amphibian declines, much of this work was correlative and potentially explained by confounding variables, such as non-native fish or disease (Hayes and Jennings 1986), or was experimental (Lawler et al 1999, Adams 2000, which may amplify effects not seen in the wild. In field studies within the Pacific Northwest, most studies have found no effect of bullfrog presence on native amphibian species occurrence (Richter and Azous 1995, Adams et al 1998, 2011, Adams 1999, Pearl et al 2005, but see Rowe et al 2019). It is possible that our native amphibian assemblage was not as susceptible to bullfrogs due to their use of terrestrial habitats post-metamorphosis.…”
Section: Discussionmentioning
confidence: 86%
“…, but see Rowe et al. ). It is possible that our native amphibian assemblage was not as susceptible to bullfrogs due to their use of terrestrial habitats post‐metamorphosis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations